Design and validation of a wheel-rail adhesion simulator in PLS-Circulator. Issue 1 (1st October 2022) - Chen, Chao; Tian, Chun; Huang, Ting Xiang; Zhu, Wen Liang
Abstract: A 1:4 scaled test rig called 'PLS-Circulator' is introduced for wheel-rail contact research under large slip conditions, which is composed of two wheel assemblies, 2 m diameter ring track with sprinklers surrounded, gearbox and two servo motors. On this basis, a wheel-rail adhesion simulator was designed to generate and measure the wheel-rail contact force. The slip ratio is the specific value of two motor speeds, which brings convenience to precisely control. SIMPACK simulation results showed that the slip ratio converged to the target value after the initial time in consideration of gear meshing vibration. The validation of the adhesion recovery was carried out utilizing PLS-Circulator under large slip conditions. Experimental results showed that in both steady and dynamic slip ratio experiments the adhesion coefficient could increase up to 26% from a lower adhesion caused by wet wheel-rail interface at the vehicle velocity of 20 km/h.